ECPAT's Efforts in Handling Child Sex Tourism Cases in Indonesia 2018 - 2020 (Case Study: Bali) - Sari, Vicki Monica; Rifa’i, Maulana; Gustianti, Nurbani Adine (International Journal of Education, Information Technology, and Others, 2024)
The basis of this research is inspired by the rapid growth of tourism activities and technological development that are increasingly accesible. Therefore, it is easy for foreigners to carry out the Child Sex Tourism cases in several regions, currently it will be focused on areas of Bali that are visited by many foreigners for vacation. The growing progress of tourism that leads to commercial sexual exploitation of children must be concern of the government and non-governmental organizations that can help eradicaate Child Sex Tourism. This organization is called ECPAT, which is an international organizational that assists and responds to cases of child exploitation or sexual crimes. This research is used human security theory and behavioralism approach. Research methodology uses qualitative research with literature study techniques sourced from several literature such as articles, journals, annual reports from various institutions and real data to support the research. The research conducted can be supported by justice and spreading education on social media.